The Eco Ladder for energy management: a literature review of economic driving and energy management - Nævestad, Tor-Olav; Hesjevoll, Ingeborg Storesund (Frontiers in Future Transportation, 2023)
Transport accounts for nearly 25% of man-made emissions of greenhouse gases, and goods transport by road accounts for 45% of the total energy consumption in transport. Measures within goods transport will therefore be a good starting point for reducing greenhouse gas emissions. Existing research shows that trucking companies’ measures to facilitate an economic driving style can achieve between 5% and 10% reduction in fuel consumption. They can probably reduce their energy consumption even more, by focusing on factors additional to driving style. However, existing recipes for such measures (e.g., ISO: 50001) seem to be relatively complicated, resource-intensive, and to a small extent adapted to transport. Previous research shows low implementation of such management systems in trucking companies, because most of them are small (<5 employees), and probably have few resources when it comes to economy, time and expertise. The aim of the study, is therefore to develop a research-based model of how trucking companies can work with economic driving and energy management at the organizational level. The model is based on a systematic review of measures for economic driving and energy management in trucking companies. The model is referred to as the Eco Ladder for energy management, and describes an approach with gradual introduction of specific measures. Companies must start with the measures that are assumed to have the greatest effect, and which are easiest to implement, before moving on to the next level. Based on existing research, we discuss expected effects for economy, emissions, traffic safety and working environment.